THE ART OF MUSIC IN THE EAST (IX-XII CENTURIES) - Madaminov Nasim Xoljo'raevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article describes the musical views of the existing musical instruments during the Arab invasion in Central Asia, the works of encyclopedic scientists who lived and worked during the first Renaissance, and their musical views.